2011
DOI: 10.1002/ccd.23005
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular approach to treat ascending aortic pseudoaneurysm in a patient with previous CABG and very high surgical risk

Abstract: Pseudoaneurysm of the ascending aorta is an uncommon pathology and a challenge in high-risk patients who undergo conventional surgery because of high operative morbidity and mortality. Endovascular exclusion of an aortic pseudoaneurysm using an endoprosthesis is a less invasive approach, but few such cases have been reported. Moreover, the use of this approach poses unique therapeutic challenges because there is no specific endoprosthesis for ascending aortic repair, particularly to treat patients with previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(17 reference statements)
0
12
0
1
Order By: Relevance
“…2 Several less invasive endovascular approaches for closure of these pseudoaneurysms have been reported, especially in surgical high-risk patients. [3][4][5][6] Our patient initially presented with an incidentally detected pseudoaneurysm of the ascending thoracic aorta, 25 years following aortic root repair and mAVR. At that time, coil embolization was performed with technically good result.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2 Several less invasive endovascular approaches for closure of these pseudoaneurysms have been reported, especially in surgical high-risk patients. [3][4][5][6] Our patient initially presented with an incidentally detected pseudoaneurysm of the ascending thoracic aorta, 25 years following aortic root repair and mAVR. At that time, coil embolization was performed with technically good result.…”
Section: Discussionmentioning
confidence: 98%
“…Several endovascular treatment options have been reported and include ascending aortic stent grafts, percutaneous coil embolization, direct thrombin injection, and off-label use of septal closure devices and vascular plugs. [3][4][5][6] We report a successful closure of a reopened, asymptomatic ascending aortic pseudoaneurysm with the off-label use of a type II Amplatzer vascular plug (AVP) in a patient 8 years after closure with coil embolization and 33 years after the initial cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently published a series of five clinical cases and described the technique in which the axillary artery was used to deliver the endograft for the treatment of different thoracic aortic diseases [9]. We also demonstrated the possibility of concomitant treatment of ascending aorta disease and coronary stent implantation [10,11].…”
Section: Access and Techniquementioning
confidence: 99%
“…Two articles provided interesting data about 3 patients treated with ascending aorta endograft implantation combined with percutaneous coronary treatments [23,25]. Moreover, Allen et al [15] reported 1 patient with severe aortic valve stenosis and concomitant acute ascending aorta penetrating ulcer with tamponade.…”
Section: Combined Proceduresmentioning
confidence: 99%